The Impact of BI Interest Rate and Amount of Money Supply on Inflation in Indonesia During 2017-2019 - Putri Sari Silaban; Dita Natania Harefa; Januarti Ira Melenia Napitupulu; Jessica Putri Br. Sembiring (Media Ekonomi dan Manajemen, 2021)
The economic progress of a country is surely influenced by its economic indicators. This indicator is an important thing to pay it attention. One of the economic indicators is inflation. Inflation will affect the economy aggregately. Due to the increase in inflation and inflation instability, it will indicate that the level of prices for goods and services in a country is high. In the end, this will have an impact on people's interest in buying these goods or using these services. Of course, the large impact will be sustainable on national income. Therefore, this study aims to analyze the effect of interest rates and the money supply on inflation in Indonesia in 2017-2019. The types of data used in this study are quantitative data and the data sources used are taken from BPS for the 2017-2019 period. .The final result of this study showed that based on the results of the analysis, it could be concluded that interest rates and the amount of money have an impact on inflation with a significance value of 0,000296. Meanwhile, the t-test results indicate that interest rates and the money supply have an impact on inflation, respectively, with values of significance areÂ  0.0371 and 0.0286.